The Influence of Communication Style, Emotional Intelligence, and Organizational Culture on Conflict Management - Lina Herlina (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study explores the influence of communication style, emotional intelligence, and organizational culture on workplace conflict management, aiming to understand how these variables collectively foster a productive and harmonious environment. Methodology/approach: This research using a literature review method, ten peer-reviewed journal articles from the last five years were analyzed, sourced from databases such as Emerald Insight, ScienceDirect, ProQuest, and Taylor & Francis. The review includes empirical studies across diverse organizational contexts—construction, multinational corporations, and public institutions—employing both qualitative and quantitative approaches. Results/findings: The findings indicate that communication style significantly shapes how conflicts arise and are addressed. Emotional intelligence enables individuals to manage disputes with empathy and adaptability. Organizational culture serves as a moderator, with inclusive and collaborative cultures promoting more constructive conflict resolution. Conclutions: The study concludes that effective conflict management emerges from the synergy of communication style, emotional intelligence, and organizational culture. Organizations that cultivate these aspects tend to enhance resilience, cooperation, and innovation. Limitations: The study relies on secondary data, with limited coverage of all industrial sectors, and findings may be more relevant to certain cultural or organizational contexts. Contribution: This research enriches organizational behavior, human resource management, and intercultural communication studies by integrating emotional, communicative, and cultural perspectives on conflict management. Insights from this review can inform managers, HR practitioners, and academics in developing organizational interventions and leadership training programs aimed at fostering constructive conflict resolution.